2014
DOI: 10.1136/bmjopen-2013-004319
|View full text |Cite
|
Sign up to set email alerts
|

Certification for vision impairment: researching perceptions, processes and practicalities in health and social care professionals and patients

Abstract: ObjectivesTo explore the patient experience, and the role of ophthalmologists and other health and social care professionals in the certification and registration processes and examine the main barriers to the timely certification of patients.DesignQualitative study.SettingTelephone interviews with health and social care professionals and patients in three areas in England.Participants43 health and social care professionals who are part of the certification or registration process. 46 patients certified as sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…A qualitative study conducted on recently certified patients reported that while certification was a life changing event, the help they received as a result substantially improved their lives. 12 It is important to note that certification figures closely reflect new registrations with local authority Social Services registers but there remains uncertainty as to how well certification data map to the actual burden of sight loss in the population. 13,14 CVI data are, however, the source for the Public Health Outcome Framework indicators for sight loss in England reported annually online (CVI rates per 100k population at risk for AMD, Glaucoma, and Diabetic Eye Disease) and are also reported by the Welsh government.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted on recently certified patients reported that while certification was a life changing event, the help they received as a result substantially improved their lives. 12 It is important to note that certification figures closely reflect new registrations with local authority Social Services registers but there remains uncertainty as to how well certification data map to the actual burden of sight loss in the population. 13,14 CVI data are, however, the source for the Public Health Outcome Framework indicators for sight loss in England reported annually online (CVI rates per 100k population at risk for AMD, Glaucoma, and Diabetic Eye Disease) and are also reported by the Welsh government.…”
Section: Discussionmentioning
confidence: 99%
“…Certification and registration is transformative for adults as the referral to social services and the support triggered substantially improves their lives. 1 While for infants and children, social services often have an important role to play, and registration also brings financial and practical benefits to families, the main provider of support is the local authority specialist vision impairment (VI) education service. Early assessment and interventions (eg, low-vision aids) can decrease risks of delayed development in motor, cognitive, language and social domains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it examines the impact of waiting for referrals to education and provides examples of good practice and identifies ways of ensuring prompt referrals. The research follows on from previous research on adults and the CVI and registration process 1 (see box 1 ), whereas the aim of this research was to examine issues related to the certification and registration processes in infants and young people.
The certification and registration processes Certification and registration are two separate processes and involve a number of stages.
…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to certification have been evaluated (Boyce et al., ) and include uncertainty on when to certify, external pressures to reduce certification rates, perception of certification being the end of process rather than a route to services, poor awareness of benefits, incorrect assumptions about patients' views and lack of clarity regarding payment. Boyce and colleagues outline recommendations to address these barriers (). However, the barriers in detection of hemianopia and referral to vision services from stroke units must also be addressed.…”
Section: Discussionmentioning
confidence: 99%